Exploring the Role of Organizational Behavior in Shaping Effective Marketing Strategies for Business Financial Enhancement - Guterres, Aida dos Santos; Pangilinan, Angelyn M. (International Humanity Advance, Business & Sciences, 2024)
This study explores the critical role of organizational behavior and marketing strategies in enhancing a company's financial performance within the context of increasing business competition. Organizational behavior is essential for aligning individual and group actions with organizational goals, which directly influences business efficiency and effectiveness. Marketing management, on the other hand, is a key process that involves identifying market targets, analyzing consumer needs, and implementing strategies that satisfy these needs, ultimately driving profitability. In the digital era, businesses face heightened competition, necessitating a strategic focus on customer satisfaction and brand positioning. This research analyzes the intersection of organizational behavior and marketing strategies, emphasizing the importance of a cohesive approach to organizational dynamics and market orientation. By integrating findings from recent studies, this paper highlights the urgency of adopting effective marketing strategies influenced by organizational behavior to improve financial outcomes and maintain competitive advantage in rapidly evolving markets.